IMPLEMENTASI GOOD COORPORATE GOVERNANCE PADA RS. ORTHOPEDI DAN TRAUMATOLOGY SURABAYA - Zaeni, Mochammd; Sawarjuwono, Tjiptohadi (FEBI IAIN Langsa, 2019)
This study aims to determine the implementation of good coorporate governance at RS. Orthopedi dan Traumatology Surabaya. The research method used is descriptive qualitative. The result of this strudy are RS. Orthopedi dan Traumatology Surabaya has not implemented good cooporate governance as a whole. Hospitals still have shortcomings in the implementation of the principles of fairness, transparency and accountability. Hospitals have not presented ﬁ nancial statements transpar ently to directors and minority shareholders and hospitals have not applied the principle of accountability as a whole because they do not have SPI to carry out the supervisory function.